Determinants Of Adolescent Girls' Knowledge And Attitudes Towards The Consistency Of Blood Supplement Consumption - Musfiroh, Sri (Ann Publisher, 2025)
Background. Anemia in adolescents is a significant global health problem. According to the World Health Organization (WHO), the prevalence of anemia in adolescents worldwide ranges from 40% to 88% of the total adolescent population, which reaches 1.2 billion people, or about 18% of the world's population. Aims. This study aims to analyze the relationship between the knowledge and attitudes of adolescent girls and adherence to blood supplement tablet consumption by 2025. Methods. This study uses a quantitative approach with an analytical descriptive design. This design was chosen to analyze the relationship between independent variables (adolescent girls' knowledge and attitudes about anemia) and dependent variables (adherence to the consumption of blood-boosting tablets). Conclusion. These findings underscore the need for a holistic approach that combines enhanced knowledge with strategies to address environmental and behavioral barriers, thereby improving the consistency of blood booster supplement consumption. Implementation. The results of this study are expected to contribute to efforts to prevent anemia through increasing compliance with TTD consumption.